Immunogenicity/Hypersensitivity of Biologics. (January 2014) - Leach, Michael W.; Rottman, James B.; Hock, M. Benjamin; Finco, Deborah; Rojko, Jennifer L.; Beyer, Joseph C.
This continuing education course was designed to provide an overview of the immunologic mechanisms involved in immunogenicity and hypersensitivity reactions following administration of biologics in nonclinical toxicity studies, the methods used to determine whether such reactions are occurring, and the associated clinical and anatomic pathology findings. Hypersensitivity reactions have classically been divided into type I, II, III, and IV reactions; type I and III reactions are those most often observed following administration of biologics. A variety of methods can be used to detect these reactions. Antemortem methods include hematology; detection of antidrug antibodies, circulating immune complexes and complement fragments, and immunoglobulin E in serum; tests for serum complement activity; and evaluation of complement receptor 1 on erythrocytes. Postmortem methods include routine light microscopy and electron microscopy, which can demonstrate typical findings associated with hypersensitivity reactions, and immunohistochemistry, which can detect the presence of immune complexes in tissues, including the detection of the test article. A final determination of whether findings are related to a hypersensitivity reaction in individual animals or across the entire study should rely on the overall weight of evidence, as findings indicative of these reactions are not necessarily consistent across all affected animals.